DAYA SAING EKSPOR PRODUK KELAPA INDONESIA DI PASAR INTERNASIONAL - Yan Subekti; Syaiful Hadi; Ermi Tety (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
This study aims to analyze the competitiveness of Indonesian coconut products inthe world market. This study used secondary data for the export of Indonesian,Philippine, Indianand World coconut products during theperiod 2000 - 2016. Datawere analyzed by usingTrade Specialization Index (ISP), the Revealed ComparativeAdvantage (RCA) and Constant Market Share analysis (CMSA). The results of thisstudy indicate that the export of Indonesian coconut products tends to increaseevery year. Indonesia has a strong competitiveness as an exporting country ofcoconut products and very mature categories in the trading of coconut products.Indonesia and Philippines has a comparative advantage as shown by the positivevalue of RCA. Indonesia's competitiveness is heavily influenced by the effect ofstandard growth as indicated by the average of positive standard growth values. Thecompetitiveness of coconut products is also heavily influenced by the effects ofstandard growth.